PENINGKATAN KOMPETENSI PROFESIONAL GURU MATEMATIKA PENGAJAR SANTRI MELALUI PELATIHAN TERSTRUKTUR - Triana Harmini; Dihin Muriyatmoko; Aziz Musthafa; Faisal Reza Pradhana; Oddy Virgantara Putra; Widya Kurniawan; Eko Prasetio Widhi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service research aims to address the low professional competence of mathematics teachers at the Darussalam Gontor Putri Modern Islamic Boarding School Campus 3, where the majority of teachers (75%) have non-science backgrounds. The intervention was carried out through a Structured Training model consisting of four sessions that focused on strengthening key mathematical concepts (Circles, Trigonometry, and Function Limits) and Problem-Based Learning (PBL) model training for pedagogical integration. The activity involved 20 teachers and was evaluated using a Pre-Test and Post-Test. The initial Pre-Test results showed an average professional competence score of only 58.5 (out of 100). Following the intervention, quantitative analysis using n-Gain revealed a significant increase in competence, with most participants reaching the Medium category and 6 participants achieving the High category (n-Gain ≥ 0.70). In addition, 95% of participants successfully designed innovative PBL-based lesson plans. In conclusion, the structured training model proved effective in addressing teachers' specific knowledge gaps, while enhancing instructional planning skills, thereby significantly increasing teachers' professional readiness to create a productive learning environment.